Accuracy Test of Qibla Direction of Qowiyuddin Mosque Jagir Wonokromo Surabaya - Anaam, Khairul; Isna Putri Sa’adah; Asri Arum Sari; Naurah Kamilah; Imroatul Mufidah; Nur Lailatul Qodriyahf (Universitas Islam Negeri Mataram, 2024)
This study was conducted to examine the accuracy of the Qibla direction of Masjid Qowiyuddin in Jagir Wonokromo, which is a crucial aspect of performing prayers (shalat) for Muslims. The instruments used in this research included the Mizwala Qibla Finder, Right-Angled Triangle, and Theodolite, each serving to ensure the precise measurement of the Qibla direction. Using a descriptive qualitative approach, the researcher collected primary data through interviews and direct field measurements, as well as secondary data from various literature references. The results showed a deviation in the Qibla direction by 23°49'12